Sistem Kendali Intensitas Cahaya Lampu Penerangan Jalan Umum Menggunakan Transformator Variabel Berbasis Arduino Uno - Lianda, Jefri; Adam, Adam; Amri, Hikmatul; Custer, Johny (Faculty of Engineering, Universitas Tanjungpura, 2020)
This research discusses the Arduino Uno based public street lighting intensity control system. The street lighting technology applied so far is still conventional technology that is classified as wasteful of energy because it still uses a continuous lighting system or an On-Off system. PJU problems arise because of too much power consumption caused by the use of large power lamps and lamp operating times. This research utilizes Arduino Uno and RTC to control the value of the variable voltage output transformer based on time division. This system has been able to control the voltage of 400 watt sodium lamps. Â The output voltage of the transformer has been divided into three levels, namely level 1, level 2 and level 3. The division of this level is based on the operating time of the lights, namely level 1 at 1830 WIB to 2200 WIB, level 2 at 2201 WIB until 2359 WIB, level 3 at 0000 WIB until 0530 WIB. Transformer output voltage at level 1 can be 220 volts. The output voltage of the transformer at level 2 can be 210 volts. Transformer output voltage at level 3 can be 200 volts. The intensity of the 400 watt sodium lamp light at level 1 is an average of 99.9 lux. The intensity of the 400 watt sodium lamp light at level 2 is an average of 85.45 lux. The intensity of the 400 watt sodium lamp light at level 3 is an average of 78.6 lux.